1993
DOI: 10.1017/s0890037x00027810
|View full text |Cite
|
Sign up to set email alerts
|

Response of Quackgrass (Elytrigia repens) Biotypes to Primisulfuron

Abstract: Quackgrass biotypes collected from 15 locations exhibited differential response to primisulfuron at 20 g ha−1in field experiments at Hudson, NY during 1990 and 1991. Quackgrass control ranged from 23 to 100% 77 days after application (DAA) in 1990 and from 38 to 100% 88 DAA in 1991. The biotype from Montpelier, OH was the most tolerant both years. Differential response of quackgrass biotypes from five locations was confirmed in greenhouse experiments. The primisulfuron rate required to reduce shoot regrowth by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Targeted weedy plants can be exposed to a low, below‐label herbicide dose, for example, if there is deliberate underdosing, tardy treatment time (oversized plants) or treatment under suboptimal environmental conditions. Most weedy plant species have significant genetic variability, including variability in response to herbicide dose . Here, we are concerned with the evolutionary impacts of herbicide use at doses (low) that enable survivors that can reproduce.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted weedy plants can be exposed to a low, below‐label herbicide dose, for example, if there is deliberate underdosing, tardy treatment time (oversized plants) or treatment under suboptimal environmental conditions. Most weedy plant species have significant genetic variability, including variability in response to herbicide dose . Here, we are concerned with the evolutionary impacts of herbicide use at doses (low) that enable survivors that can reproduce.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts have shown that weed populations can vary greatly in susceptibility to a herbicide (e.g. Bourdot et al, 1990;Cerdeira and Duke, 2006;DeGennaro and Weller, 1984;Ellis and Kay, 1975a;1975b;Gillespie and Vitolo, 1993;Jacobsohn and Andersen, 1968;Patzoldt et al, 2002;Price et al, 1983;1985;Somody et al, 1984;Tardif andLeroux, 1991a Thai et al, 1985;Tranel and Trucco, 2009). Hence, knowledge about the magnitude of such inter-population differences will be pivotal when assessing creeping resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, based on these GR50 values for fresh weight, the population CC1 was about 3.9 and 2.6-fold more susceptible to nicosulfuron than population CC2 in 1 st and 2 nd year, respectively, but differences were not so prominent when based on other parameters (plant height, leaf area and ALS activity), ranging from 1.18 to 1.8-fold. As previous investigations have shown that weed populations can vary greatly in susceptibility to herbicides (DeGennaro and Weller, 1984;Gillespie and Vitolo, 1993;Patzoldt et al, 2002), the differences between population CC1 and CC2 could be attributed to inter-population variability in susceptibility to nicosulfuron, though these differences could be the consequence of repeated application of ALS herbicides to the CC2 population during the six previous years. Future investigations are necessary in order to clarify this dilemma and give recommendation for their control in integrated weed management system.…”
Section: Discussionmentioning
confidence: 92%